Can increased load carriage affect lower limbs kinematics during military gait?. Issue 9 (2nd September 2022) - Sousa, Manoela Vieira; Sebastião, Ricardo; Fonseca, Pedro; Morais, Sara; Soares, Denise; de Sousa, Inês; Machado, Leandro; Sousa, Filipa; Vaz, Mário; Vilas-Boas, João Paulo
Abstract: The aim of this study was to investigate if increased load carriage, in male military personnel, can affect the lower limbs kinematics. Twelve male military volunteers from the Portuguese Army were recruited and evaluated in an unloaded and loaded gait condition. Linear kinematics and lower limbs joint angle at heel strike, midstance and toe off were calculated. The stance, swing and double support times were found to be different between load conditions ( p < 0.05). There was an interaction between load and limb ( p < 0.05) for joint angles, during midstance, with limbs performing different movements in the frontal plane during loaded gait. Load increase had a different effect on the right knee, with a reduction in the abduction ( valgus ). This study may be beneficial in offering suggestion to improve the performance of gait with load and in an attempt to help prevent possible injuries. Practitioner summary: Increased load can affect lower limbs of male soldiers at the pelvic, hip and knee angles on the frontal plane, which can alter the joint force distribution. While these alterations may indicate protective mechanics, load management procedures should be implemented along with gait monitoring to avoid negative effects in performance.